2007
DOI: 10.1590/s0066-782x2007001700010
|View full text |Cite
|
Sign up to set email alerts
|

Caso 6/2007: criança de dez anos com estenose pulmonar valvar discreta

Abstract: A ten-year-old white male child who had been diagnosed with a heart murmur at six months of age in a routine examination and remained asymptomatic, active and with no physical limitations. On physical examination he was eupneic and with normal pulses. He weighed 47 kg and was 147 cm tall. His blood pressure was 110/70 mm Hg and heart rate was 76 bpm. No cyanosis was observed. The aorta was not palpable in the suprasternal notch. Chest examination showed neither deformities nor cardiac impulses, and a valve and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For example, Arquivos Brasileiros de Cardiologia presented the following sections: Anatomopathological Session (sic), Clinical Radiological Session (sic), Brief Comments, In Memoriam, Point of View, Image, Clinical Update and Guideline. [8][9][10][11] In Revista Brasileira de Cirurgia Cardiovascular, different sections were found, for example: Special Article, Brief Communication, Clinical Surgical Correlation and Experience of the Service. [12][13][14] Among the articles appearing in sections with different names in Arquivos Brasileiros de Cardiologia, there were two in the Clinical-Radiographic Correlation section that in reality were case reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Arquivos Brasileiros de Cardiologia presented the following sections: Anatomopathological Session (sic), Clinical Radiological Session (sic), Brief Comments, In Memoriam, Point of View, Image, Clinical Update and Guideline. [8][9][10][11] In Revista Brasileira de Cirurgia Cardiovascular, different sections were found, for example: Special Article, Brief Communication, Clinical Surgical Correlation and Experience of the Service. [12][13][14] Among the articles appearing in sections with different names in Arquivos Brasileiros de Cardiologia, there were two in the Clinical-Radiographic Correlation section that in reality were case reports.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Among the articles appearing in sections with different names in Arquivos Brasileiros de Cardiologia, there were two in the Clinical-Radiographic Correlation section that in reality were case reports. 8,9 In the Brief Comments, one cohort study was found. 11 One of the strong points of the present study was that it made comparisons between recent, simultaneously published journals within the same field, in the same country, without apparent conflicts of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation